Bibliographic exchange in Malaysia: variations in name headings - Mansor, Yushiana (Emerald Group Publishing Limited ., 2003)
Studies the prospect of bibliographic exchange among libraries in Malaysia. Investigates the compatibility of MARC records as prepared by selected Malaysian academic libraries. Reports on the different cataloguing practices found in preparing name headings, i.e. MARC fields “1XX” and “7XX”. Results of the study exemplified different cataloguing practices among Malaysian cataloguers.